Pregled jezikoslovnih zapisov o slovenščini v neslovničnih knjižnih in rokopisnih delih 1672-1758 - Ahačič, Kozma (Slavistična revija, 2009)
The article (as first of two) provides a survey of linguistic attestation of Slovene in non-grammar publications and manuscripts by Janez Ludvik Schönleben, Matija Kastelic, Janez Vajkard Valvasor, Janez Svetokriški, Gregor Vorenc, and Hipolit Novomeški. Every text is furnished with a short introduction, an annotated translation to Slovene (or annotated transcription of the Slovene text), detailed analysis, information on the influence of the previous texts, influence of the treated fragment on the texts that followed, and a survey of literature concerning the treated fragment.
Keywords: grammar; Hipolit Novomeški, 1650-1722; Janez Svetokriški, 1645-1714; Kastelec, Matija, 1620-1688; naglaševanje; orthography; pravopis; Schönleben, Janez Ludvik, 1618-1681; Slovene; slovenščina; slovnica; Valvasor, Janez Vajkard, 1641-1693; Vorenc, Gregor; zgodovina jezika